The transmembrane adaptor protein NTAL limits mast cell chemotaxis toward prostaglandin E2 - Halova, Ivana; Bambouskova, Monika; Draberova, Lubica; Bugajev, Viktor; Draber, Petr (Science signaling, 2018)
Chemotaxis of mast cells is one of the crucial steps in their development and function. Non-T cell activation linker (NTAL) is a transmembrane adaptor protein that inhibits the activation of mast cells and B cells in a phosphorylation-dependent manner. Here, we studied the role of NTAL in the migration of mouse mast cells stimulated by prostaglandin E2 (PGE2). Although PGE2 does not induce the tyrosine phosphorylation of NTAL, unlike IgE immune complex antigens, we found that loss of NTAL increased the chemotaxis of mast cells toward PGE2 Stimulation of mast cells that lacked NTAL with PGE2 enhanced the phosphorylation of AKT and the production of phosphatidylinositol 3,4,5-trisphosphate. In resting NTAL-deficient mast cells, phosphorylation of an inhibitory threonine in ERM family proteins accompanied increased activation of β1-containing integrins, which are features often associated with increased invasiveness in tumors. Rescue experiments indicated that only full-length, wild-type NTAL restored the chemotaxis of NTAL-deficient cells toward PGE2 Together, these data suggest that NTAL is a key inhibitor of mast cell chemotaxis toward PGE2, which may act through the RHOA/ERM/β1-integrin and PI3K/AKT axes.
Keywords: fosforylace; Cholesterol; Actins; Protein Domains; threonin; Phosphorylation; bodová mutace; Dinoprostone; Chemotaxis; Animals; integriny; Phosphatidylinositol 3-Kinases; Mast Cells; mastocyty; Mice; cholesterol; Adaptor Proteins, Signal Transducing; proteinové domény; Integrins; chemotaxe; antigeny CD29; Membrane Proteins; zvířata; membránové proteiny; Proteins; adaptorové proteiny signální transdukční; Integrin beta1; proteiny; Point Mutation; Threonine; Signal Transduction; dinoproston; fosfatidylinositol-3-kinasy; aktiny; signální transdukce; myši